2015
DOI: 10.1007/s10620-015-3888-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Plays a Pivotal Role in Chemically Induced Hepatocellular Carcinoma in Mice

Abstract: These results demonstrated that IL-17A plays a pivotal role in chemically induced hepatic carcinogenesis, which is most likely through inflammation-initiated oxidative DNA damage and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…It plays a crucial role in the induction of proinflammatory cytokines, chemokines, metalloproteases, and other mediators of the immune system. [45][46][47][48] In addition, IL-17A also plays an important role in the progression of pulmonary diseases. Ding et al 49 reported that IL-17A can facilitate pulmonary inflammation and that it may play an important role in the process of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in the induction of proinflammatory cytokines, chemokines, metalloproteases, and other mediators of the immune system. [45][46][47][48] In addition, IL-17A also plays an important role in the progression of pulmonary diseases. Ding et al 49 reported that IL-17A can facilitate pulmonary inflammation and that it may play an important role in the process of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators pointed out the pivotal role of inflammatory modulation in the progression of hepatocellular carcinomas [20]. The inflammatory cytokines including TNF- α , IL-6, and IL-1 β were overproduced in hepatic injury [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-17A regulates the development of stem cell features in both mouse and human pancreatic cancer models and critically contributes to tumor growth and progression (McAllister et al, 2014;Zhang et al, 2018). Intriguingly, IL-17 can also promote the expansion of liver progenitor cells to promote liver regeneration (Guillot et al, 2018); the absence of IL-17 signaling ablates tumorigenesis in a chemical-induced hepatocellular carcinoma (Sun et al, 2016), an inflammation-driven liver cancer model. This IL-17-driven cellular mechanism linking tissue repair to tumorigenesis probably also applies to colon cancer.…”
Section: Il-17-induced Mitogenic Signaling and Cancermentioning
confidence: 99%